FMD: A parallel library for performing classical molecular dynamics simulations - Arham Amouye Foumani (SoftwareX, 2024)
In this paper, the MPI-based parallel library Free Molecular Dynamics (FMD) is introduced. The general structure of a typical program utilizing FMD to perform classical molecular dynamics (MD) simulation is described. Much of the paper is devoted to one of the advanced features of FMD: its ability to compute physical fields defined on distributed grids (a.k.a. “turies”). Each cell of a distributed grid may be shared among any number of MPI processes. Distributed grids can be used to combine MD with continuum models or to obtain macroscopic quantities, e.g. density, as functions of time and space. The library is designed to provide an easy to use interface for its users, as well as equip its developers with reusable tools required for expanding the code.